Stereotype und Affektivität im interkulturellen Fremdsprachenunterricht - Pieklarz, Magdalena (Glottodidactica, 2006)
The following article discusses the relation between cultural stereotyping and affective processes in education leading to intercultural communication in modern languages studies. This work is both an attempt to explain this phenomenon theoretically and to research the previously mentioned relation in the light of postulates of intercultural education. A part of this work is also an analysis aiming at determining the factors influencing a stereotype category.